T-2 mycotoxin intoxication in piglets: a systematic pathological approach and apoptotic immunohistochemical studies - Quiroga, María A.; Risso, Miguel A.; Perfumo, Carlos J. (Brazilian Journal of Veterinary Pathology, 2009)
An experimental study was performed in order to analyze the histopathological findings of gastrointestinal mucosa and regional lymph-nodes in piglets intoxicated with T-2 toxin as well as the mechanism of T-2 induced apoptosis in the intestinal crypt epithelia. Sixteen piglets were divided into 4 groups receiving a single oral administration of T-2 toxin. Group A: 2.5 mg T-2/kg b.w.; group B: 2 mg T-2/kg b.w.; group C: 1.5 mg T-2/kg b.w.; group D: control group without toxin. Organ lesions were classified in grades 0 to 4 according with severity and were statistically analyzed. Apoptosis was examined in intestinal sections only in groups A and D. Group A piglets showed clinical signs and pathological changes related with those seen in circulatory shock. Microscopic lesions were observed only in pigs from groups A and B. In stomach, lesions consisted of congestion, hemorrhages and necrotic cells in the isthmus and neck regions. Submucosal edema and necrotic crypt epithelial cells were seen in duodenum, jejunum, ileum, cecum and colon. The greatest grade of lesions was observed in colon. In lymph node, grade of lymphocytes depletion and necrosis was significantly higher in cortex than paracortex. Apoptotic bodies were present in intestinal crypt cells, lymphoid cells from lamina propria and ileal Peyer´s patches. Apoptosis seems to be the mechanism involved in the development of intestinal lesions.